Optimisation study on refinery process operations for a petroleum company - Tan, Terence Tock Hwee. (2008)
This dissertation takes a closer look at the modelling of the refinery complex and how the model is utilised in different scenario analyses. The refinery yield and quality patterns are given the degree of freedom to randomise in the model optimisations using the Excel "Solver" program.